Advances in computers., volume 64, New programming paradigms - Zelkowitz, Marvin V., 1945- (Amsterdam ; Boston : Elsevier Academic Press, 2005)
The series covers new developments in computer technology. Most chapters present an overview of a current subfield within computer science, with many citations and often include new developments in the field by the authors of the individual chapters. Topics include hardware, software, theoretical underpinnings of computing, and novel applications of computers. This current volume emphasizes the role of the internet, the world wide web and other aspects of a distributed computing environment. Open source development as well as computing for the handicapped are additional important topics. Key Features: - In-depth surveys and tutorials on new computer technology. - Well-known authors are researchers in the field. - Extensive bibliographies with most chapters. - Important chapters on new technologies for software development: open source development and the technology needed to use the web for electronic commerce. * In-depth surveys and tutorials on new computer technology. * Well-known authors are researchers in the field. * Extensive bibliographies with most chapters. * Important chapters on new technologies for software development: open source development and the technology needed to use the web for electronic commerce.
Automatic evaluation of web search services / Abdur Chowdhury -- Web services / Sang Shin -- A protocol layer survey of network security / John V. Harrison and Hal Berghel -- E-service : the revenue expansion path to e-commerce profitability / Roland T. Rust, P.K. Kannan, and Anupama D. Ramachandran -- Pervasive computing : a vision to realize / Debashis Saha -- t Open source software development: structural tension in the American experiment / Coskun Bayrak and Chad Davis -- Disability and technology : building barriers or creating opportunities? / Peter Gregor, David Sloan, and Alan F. Newell.
Includes bibliographical references and indexes.
Keywords: World Wide Web; Computer software -- Development; User interfaces (computer systems).; Computer software; Computer science; Library science; Electronic books